PENGARUH NEW NORMAL DITENGAH PANDEMI COVID-19 TERHADAP PENGELOLAHAN SEKOLAH DAN PESERTA DIDIK - Yudi Firmansyah; Fani Kardina (BUANA ILMU, 2020)
The pandemic outbreak of Corona Virus Disease 19 (covid-19) which not only shocked the national sphere, but the international sphere was preoccupied with the presence of the covid-19 virus outbreak, this incident inhibited all activities of various human lives from various sectors, especially in the field of education, namely with teaching and learning activities both schools and college level. The policy issued by the government to get to the new normal can have a big influence in various aspects, especially in the field of education which can influence the management of schools and students towards new normal. Applications that can support the process of learning activities, such as applications: zoom, google classroom, whatsapp, and other applications. During learning in the network (DARING). Corona virus is a large part of the virus that can cause disease in humans and animals. Online learning is abbreviated as Online learning, online learning by utilizing the internet network. Students or students are one component of education that is the subject of learning. Educational staff are all members of the community who are dedicated and appointed to support the implementation of education. The school and the surrounding community have a give and take relationship. This new normal is meant to coexist with Covid-19. The Ministry of Education and Culture issues Circular No. 15 of 2020 concerning Guidelines for Conducting Learning from Home in an Emergency Spread Covid-19. the decree was very influential for the continuity of education in Indonesia by implementing new normal. Keywords: Covid-19, school management, students, new normal. Kejadian pandemi wabah Corona Virus Disease 19 (covid-19) yang tidak hanya menggemparkan lingkup nasional saja, namun ranah internasional disibukkan dengan kehadiran wabah virus covid-19, kejadian ini menghambat berbagai segala aktvitas kehidupan manusia dari berbagai sektor bidang, terutama dalam bidang pendidikan yaitu dengan aktivitas kegiatan belajar mengajar baik sekolah-sekolah maupun tingkat perguruan tinggi. Kebijakan yang dikeluarkan oleh pemerintah untuk menuju new normal tersebut dapat berpengaruh besar dalam berbagai aspek, terutama pada bidang pendidikan yang dapat pengaruhnya dalam pengelolahan sekolah dan peserta didik menuju new normal. Aplikasi yang dapat menunjang proses kegiatan belajar, antara lain seperti aplikasi: zoom, google classroom, whatsapp, maupun aplikasi lainnya. Selama pembelajaran dalam jaringan (DARING). Corona virus ini adalah bagian besar virus yang dapat menyebabkan penyakit pada manusia maupun hewan. Pembelajaran dalam jaringan (online) disingkat sebagai pembelajaran Daring, pembelajaran online dengan memanfaatkan jaringan internet. Siswa atau peserta didik adalah salah satu komponen pendidikan yang menjadi subjek dalam pembelajaran. Tenaga kependidikan adalah semua anggota masyarakat yang mengabdikan diri dan diangkat untuk menunjang penyelengaraan pendidikan. Sekolah dan masyarakat sekitarnya memiliki hubungan yang saling memberi dan menerima. new normal ini dimaknai hidup berdampingan dengan Covid-19. Kemendikbud mengeluarkan Surat Edaran No. 15 Tahun 2020 tentang Pedoman Penyelenggaraan Belajar dari Rumah Dalam Masa Darurat Penyebaran Covid-19. surat keputusan tersebut sangat berpengaruh bagi kelangsungan pendidikan di Indonesia ini dengan melaksanakan new normal. Kata Kunci: Covid-19, pengelolahan sekolah, peserta didik, new normal.